Analisis Produktivitas Alat Berat dalam Pengelolaan Sampah di Kecamatan Sukarami Kota Palembang: Analysis of Heavy Equipment Productivity in Waste Management in Sukarami District, Palembang City - Firda, Ani; Akhirini; Permatasari, Rosmalinda (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
In Indonesia, solid waste has become a problem for municipalities, which could result in hygienic and aesthetically unpleasant issues. The high rate of population growth will have an impact on waste generation since it will change the needs and lifestyles of city dwellers. The collection, transportation, and final disposal of urban solid waste (TPA) require suitable facilities and infrastructure, particularly hefty equipment. Heavy equipment, specifically waste trucks, and heavy digging equipment, plays a significant part in supporting waste management activities. In particular, the Palembang City region is covered in this study's discussion of the productivity of heavy machinery used in waste management, which might begin with the collecting system, transportation system, and heavy equipment employed at the landfill. The study was conducted in Palembang City's Sukarami District, and data was collected by surveying and observing the current condition of the heavy equipment that was already in place, namely in terms of cycle time variables and the volume of waste that was served. The findings of the study indicate that direct communal and direct individual patterns characterize the region's waste-collecting practices. Dump trucks, which are used to transport waste, had a productivity range of 609.98 to 1266.13 kilograms per hour, while bulldozers and excavators had a range of 759.42 to 1166.17 kilograms per hour. This heavy equipment repair recommendation is targeted at bulldozers and excavators since a field investigation reveals that there are now only 2 pieces of bulldozer heavy equipment and 1 unit of excavator heavy equipment available.